Towards Gender Equality in the Music Industry: Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Publishing USA, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This volume presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future.
Keywords: Music / Business Aspects; Music / Philosophy & Social Aspects; Social Science / Gender Studies; Social Science / Women's Studies

The Changing Roles of Female Visual Artists in Morocco - El Azhar, Samir (Journal of Global Initiatives: Policy, Pedagogy, Perspective, 2019)
Keywords: Myriam

Le #moiaussi de la danse - Lauzon, Véronique (2019)
Des acteurs du milieu de la danse brisent le silence sur les abus de pouvoir, le harcèlement psychologique et les agressions sexuelles vécus. Deux ans après #moiaussi, une quinzaine d’entre eux tentent de faire éclater l’omerta qui plombe cet environnement jugé toxique.
Keywords: Bibliographie; Nettoyer

Les abus et la «loi du silence» dans la danse - Morneau, Caroline (Le Journal de Québec, 2019)
Abus psychologiques, physiques, sexuels: après les milieux du cinéma et de l’humour, on réalise que celui de la danse comporte son lot de scandales.
Keywords: Bibliographie; Nettoyer

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Keywords: Bibliographie; Nettoyer

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Counting the music industry: the gender gap - Bain, V (Counting the music, 2019)

Politique de prévention et d’intervention contre l’intimidation, le harcèlement et la violence - École nationale de cirque - Montréal (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

Climat toxique dans le milieu de l’humour, malaises en conférence de presse - Piqueur, Lucie (Urbania, 2019)
Le regroupement « Pour les prochaines » souhaite en finir avec la culture du viol en humour, mais c'est pas gagné.
Keywords: Bibliographie; Nettoyer

Pour les prochaines dénonce une culture toxique en humour - Ruel-Manseau, Audrey (La Presse, 2019)
Des humoristes de la relève affirment que le milieu de l’humour reste gangréné par la culture du viol, même deux ans après le mouvement mondial #moiaussi. En mettant sur pied Pour les prochaines, les jeunes femmes souhaitent « éradiquer » les inconduites sexuelles de l’industrie, et tendent la main aux acteurs importants du monde comique afin qu’ils s’allient pour poser des actions concrètes.
Keywords: Bibliographie; Nettoyer

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Bibliographie

Formation sur le respect en milieu du travail - Conseil des Arts du Canada (2019)
Cette session d’information au sujet de milieux de travail respectueux explore les raisons derrière l’augmentation du nombre de problèmes de comportement en milieu de travail, de son impact, ainsi que de l'importance de définir les attentes en matière de comportement afin d'aider les employeurs et les organismes à gérer, contrôler et prévenir les comportements pouvant constituer du harcèlement (harcèlement sexuel, discrimination, intimidation et violence ).
Keywords: Bibliographie; Nettoyer

Tackling gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, Sam (International Journal of Cultural Policy, 2019)
Cross-disciplinary research has highlighted the persistence of gender inequalities across music scenes. However, the way in which cultural policy shapes responses to gender inequalities in music has been relatively underexplored. This article draws on research from Swedish and UK contexts, supporting analysis with reference to 9 key-stakeholder interviews from both. Comparing perspectives from ‘more’ and ‘less’ gender-equal contexts, with sufficiently different cultural policy traditions, the article explores how responses to gender inequalities in music are influenced by ‘cultural democratic’ and ‘arm’s length’ approaches. It demonstrates that, as a result of these traditions, there is a comparatively more interventionist approach in Sweden at a national level, whereas the lack of central government response in the UK has encouraged more market-oriented solutions. It suggests that this ‘arm’s length’ approach necessitates different grassroots organisational strategies in order to affect change but notes that these, alongside austerity agendas, are insufficient in the long term.
Keywords: Music policy; arm’s length; gender inequalities; interventionist; market-oriented

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs - CulturalHRC (2019)
Une ressource de formation pour les employeurs et les conseils d’administration produite par Williams HR Consulting. Cette ressource de formation en gestion d’une durée de 30 minutes expliquera comment répondre aux allégations de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - CulturalHRC (2019)
Une ressource de formation pour les artistes/travailleurs culturels/employés produite par Williams HR Consulting. Cette ressource de formation d’une durée de 30 minutes démontre les actions à prendre lorsqu’ils sont victimes ou témoins de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Consentability: Consent and its Limits - Kim, Nancy S. (Cambridge University Press, 2019)

Violence in the mosh pit: assault within the Australian punk scene - Barnes, Ash; White, Rob (Current Issues in Criminal Justice, 2019)
The mosh pit is a unique crowd formation where audience members dance aggressively to engage with the music, the performers and each other. However, in this space, Australian punks may experience violations of bodily integrity. Multiple levels and types of transgression occur, as members break with mosh pit ethics by engaging in unwanted and unlawful sexual and physical violence. This case study provides an example of how group normative behaviour is confounded in liminal spaces – how transgression within such spaces undermines the supposed freedom experienced by its participants. Whilst the mosh pit is perceived to be a site governed by its own particular ethics, some defy these in word and practice. The rules of engagement are ambiguous, and offenders are able to rationalise their harms through neutralisation techniques and the diffusion of blame and responsibility. The consequence is that more often than not, offenders can use the unique physical nature of the mosh pit to execute personal vendettas and engage in intentional violence such as ‘crowd killing’ and sexual assault, with little social and legal consequence. Moreover, a certain culture of denial permeates participant responses to these issues. Throughout it all, the violence occurring has a decidedly masculine basis, reflecting overarching gender differences in interpersonal violence generally.
Keywords: assault; cultural criminology; denial; mosh pit; punk scene

Women composers’ use of online communities of practice to build and support their careers - Hennekam, Sophie; Macarthur, Sally; Bennett, Dawn; Hope, Cat; Goh, Talisha (Personnel Review, 2019)
Purpose The purpose of this paper is to examine women composers’ use of online communities of practice (CoP) to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. Design/methodology/approach The authors employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of CoP. Content analysis was used to analyze the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. Findings The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility and develop career agency through learning and knowledge acquisition. CoP emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. Originality/value The findings suggest that online CoP can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.
Keywords: Career progression; Communities of practice; Creative industries; Gender; Mixed methodologies; Myriam; Women composers; music industry

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

Antifeminismes et masculinismes d'hier et d'aujourd'hui - Bard, Christine; Blais, Mélissa; Dupuis-Déri, Francis (Presses universitaires de France, 2019)
Antiféminismes et masculinismes d'hier et d'aujourd'hui . Aussi ancienne que les lunes féministes, l'opposition à l'émancipation des femmes est loin de n'être que le reliquat d'un passé révolu : l'anti-féminisme contemporain reste vivace et pluriel. « Printemps des pères », « Manif pour tous », « célibataires involontaires » et mobilisations contre la « théorie du genre » : il est renouvelé par des masques séducteurs, des emprunts au discours égalitaire, par un répertoire d'action actualisé et par une nouvelle militance, dite masculiniste, dans un climat politique et social propice à son extension. Pour être compris et combattus, les antiféminismes doivent aujourd'hui être situés dans une perspective historique. Leur ancrage conservateur est souligné, mais aucune famille politique - ni aucune religion - n'est immunisée. Ils ne sont pas, non plus, le monopole des hommes. En analysant diverses expressions de l'antiféminisme depuis le XIXième siècle, les contributions à cet ouvrage démontrent la vitalité historique de ce combat et mettent en évidence ses points de contact avec l'homophobie et le racisme : l'intersectionnalité des haines. L'ensemble constitue une réponse inédite en même temps qu'un appel à la vigilance.

The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Le harcèlement en milieu de travail au Québec - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Trousse à outil pour la gestion des ressources humaines : Harcèlement et violence dans le milieu de travail - Conseil des ressources humaines du secteur culturel. (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)
Ils sont tournés les uns vers les autres. Ils s'observent et s'écoutent. Ils s'échangent des idées, des armes, de l'argent ou des femmes. Dans cet univers clos réservé aux hommes, le pouvoir se relaie et se perpétue a̧ la façon d'une chorégraphie mortifère. Le boys club n'est pas une institution du passé. Il est bien vivant, tentaculaire: État, Église, armée, université, fraternités, firmes -- et la liste s'allonge. À la manière d'une chasse à l'image, c'est dans les représentations au cinéma et à la télévision que Martine Delvaux le traque. Véritable plongée en eaux noires, ce livre nous invite á considérer l'entre-soi des hommes comme un phénomène régressif. Un dispositif à profaner, déconstruire, refuser, parce que nos vies comptent

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

#MeToo and the politics of social change - Fileborn, Bianca; Loney-Howes, Rachel (Palgrave Macmillan, 2019)

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

Étude sur la rémunération des travailleurs culturels au sein des organismes artistiques et culturels québécois - Groupe-conseil Solertia (Groupe-conseil Solertia, 2019)

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Myriam; Turkey; film industry; gender; gender role; women

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

On peut plus rien dire: Militantisme à l'ère des réseaux sociaux - Lussier, Judith (Cardinal, 2019)
Consacrée par la sous-culture web, l’expression « Social justice warrior » désigne des militants nouveau genre qui semblent s’offusquer pour un rien et ne ratent aucune occasion de saisir leur clavier pour le clamer haut et fort. Ultra réactifs, ils usent de leur voix sur les réseaux sociaux pour s’attaquer aux discours qu’ils considèrent comme racistes, misogynes, spécistes ou encore classistes. Hypersensibles ou acharnés, héros ou bourreaux : qui se cache derrière la caricature? Qu’est-ce qui les motive, et surtout, comment leur démarche s’inscrit-elle dans un projet de société au 21e siècle?Directement concernée par l’appellation, Judith Lussier se plonge au cœur du phénomène, questionne ses limites et part à la rencontre de ces individus qui ont tellement à cœur de défendre leurs idéaux de justice sociale qu’ils finissent parfois par s’en rendre malades.

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Code de Conduite pour les arts de la scène au Canada - Milieux de travail respectueux dans les arts (2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Carefree or Controlled? Understanding the Night-Time Economy - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
The term ‘Night-Time Economy’ was coined in the late twentieth century (Shaw 2014) in town planning circles, and increasingly used into the twenty-first century to describe the expanding number of pubs, bars and clubs concentrated in city centres and targeting predominantly 18–24-year-olds (Roberts 2006: 332). But what exactly is the Night-Time Economy, and what role does it play in the lives of young women today? How has it changed as a site of leisure, and what does it mean to say that neoliberal forces have played a role in shaping it? What do we mean by the supposed ‘feminisation’ of the NTE, and what are the implications of this process for the ways that women engage with these spaces? This chapter charts the development of the NTE in the UK and the rise of the ‘24-hour city’, highlighting the ways in which neoliberal ideals have shaped both the landscape of the NTE and the types of behaviours and consumption practices that are expected within it. Such considerations are important for research that attends both to the wider social structures within the NTE and the individual specificities of the lives of young people as they participate in it. I will then explore the significance of space and place in research focusing on the NTE, situating the current study geographically and exploring Newcastle’s own NTE in more depth and detail.
Keywords: Charvis; Essex Girl; Geordie; Night-time Economy; Northern Identity

Conclusion - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As has become increasingly evident throughout this book, the girls’ night out clearly offers specific and nuanced ways in which to do femininities and friendships which are not present in other types of night out, and perhaps also specific types of pressures to do femininity. Whilst the NTE is increasingly recognised as a useful avenue through which to research young people’s lives, less attention has been given to the girls’ night out as a specific type of engagement with the NTE that may illuminate nuances in the ways in which young women ‘do’ gender and femininities. This book thus marks a unique contribution within a wider body of research on young people’s drinking and clubbing. This concluding chapter will pull together the main arguments outlined throughout this book, highlighting the tensions and contradictions embedded in young women’s negotiations of femininity and the ways in which these reflect the idea that the successful embodiment of ‘girly’ and ‘girliness’ is simultaneously something that is desired yet derided.
Keywords: Drinking Practices; Girly Girl; Research Young People; Time Girls; otheringOthering

Introduction - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
‘Going out’ is widely recognised as a central leisure activity in the lives of many young people (Chatterton and Hollands, Urban nightscapes: Youth cultures, pleasure spaces and corporate power. Routledge, 2003; Waitt et al., ‘The guys in there just expect to be laid’: Embodied and gendered socio-spatial practices of a ‘night out’ in Wollongong, Australia. Gender, Place & Culture, 18(2), pp. 255–275, 2011), and engaging in leisure practices in the Night-Time Economy (NTE) is likely to be an important part of women’s lives in the UK. Indeed, the ‘night on the town’ is framed in many research accounts as offering important opportunities for young women to relax, socialise with friends and escape from the often mundane realities of everyday life, work and other responsibilities (Guise and Gill, ‘Binge drinking? It’s good, it’s harmless fun’: A discourse analysis of accounts of female undergraduate drinking in Scotland. Health Education Research, 22(6), pp. 895–906, 2007; Jayne et al., Emotional, embodied and affective geographies of alcohol, drinking and drunkenness. Transactions of the Institute of British Geographers, 35(4), pp. 540–554, 2010). Yet, young women’s experiences of the NTE are also clearly shaped by neoliberal and gendered expectations around consumption, body work and self-regulation. In particular, it is important to explore in more depth how—within a supposed ‘post-feminist’ context—expectations around ‘appropriately’ feminine dress and behaviour may continue to shape the experiences of young women like Nicole in contemporary leisure spaces. But what does it actually mean and look like for young women to be ‘feminine’ today? Is this something that is relevant or important to them? How are tensions around girliness and femininity lived and negotiated in practice in women’s everyday lives? And crucially, is it still more difficult for some women to adopt ‘appropriately’ feminine identities than others? This book considers these questions and explores the ways in which women’s participation in the UK NTE continues to be constrained in a supposedly post-feminist society (Harris, Jamming girl culture: Young women and consumer citizenship. In A. Harris (ed.) All about the girl: Culture, power and identity. Routledge, 2004).
Keywords: Contemporary Femininity; Contextual Expectations; Feminine Identity; Night-time Economy (NTE); Nightlife Scene

‘It’s Girl Time’: Girliness and Friendships - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
With what Chatterton and Hollands call the ‘ritual descent’ (2002: 95) of young women into bars and clubs every weekend, we must take seriously young women’s participation in such spaces and explore further what role participating in the NTE plays in young women’s lives. Participating in the NTE has been increasingly recognised as an important component of the lives of many young women (Hollands 1995), and the participants in my study were no exception. Set against a backdrop of conflicting debates positioning the NTE as simultaneously a site of both pleasure and regulation, it is important to understand the value engaging with the NTE has for young women and the ways in which this can offer opportunities for ‘doing’ femininities or girliness and cementing friendships within these spaces. The girls’ night out represents a discreet and distinctive mode of engagement with the NTE, yet one that has received little attention in research, despite the fact that it is likely to reveal a huge amount about the individual and collective production and negotiation of femininities and friendships in nightlife venues. This chapter provides the backdrop for the remainder of the book by exploring what the girls’ night out means to young women and the central role it can play in the negotiation and maintenance of friendships and in doing ‘girly’. Whilst previous research has depicted friendships within the NTE as potentially shallow or instrumental and consumption practices as highly individualised, this chapter highlights the ways in which going out was described as an important and valued opportunity to maintain close female friendships, spend time together and enjoy opportunities to socialise and relax. I will also introduce some of the ways in which alcohol consumption was central to the young women’s negotiations of the NTE. Drinking could take on a particular role on the girls’ night out, where alcohol could function in the maintenance and cementing of friendships and the creation of intimacy (particularly when ‘pre-drinking’ at home). Consuming certain types of alcohol could also enable ‘girliness’ to be embodied in particular ways through certain consumption choices. I argue that the ‘girling’ of drinking and clubbing is particularly significant because alcohol consumption in public spaces has traditionally been recognised as a masculine pastime, rendering drinking and femininity fundamentally incompatible. If young women are able to rupture the linkages between public drinking and masculinity, they may be able to recast women’s presence and alcohol consumption in the contemporary NTE as feminine and respectable. I also explore the ways in which getting ready for a girls’ night offered further opportunities to do girliness collectively.
Keywords: Female Friends; Girlhood; Girly Girl; Time Girls; wineWine

‘People Don’t See You if You’re a Woman and You’re Not Really Dressed Up’: Visibility and Risk - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
Against a backdrop of research suggesting that young women are still expected to engage in active risk management on a night out (Brooks, ‘Guys! Stop doing it!’: Young women’s adoption and rejection of safety advice when socializing in bars, pubs and clubs. British Journal of Criminology, 51(4), pp. 635–651, 2011), this chapter will explore the centrality of understanding of space and visibility to young women’s negotiations of risk and safety in mainstream bars and clubs in Newcastle’s NTE. Visibility comes into play in two distinct ways here—firstly, as in the previous chapter, participants drew on narratives of ‘fitting in’, this time to describe the types of venues that felt comfortable and safe to them. Attending a venue where they felt out of place or ‘different’ to other patrons could leave women feeling exposed, visible and vulnerable, and these spaces were positioned as risky and dangerous. Secondly, women recognised that bars and clubs are spaces where ‘everyday’ experiences of heterosexualised violence are trivialised and normalised, and they managed their dress and appearance in particular ways in order to position themselves as less visible—or even invisible—to try to avoid ‘unwanted attention’ and harassment.
Keywords: Charvis; Posh People; Sexual Abuse Rape; Unwanted Attention; Working-class College Students

‘Rowdy…? That’s the Whole Point of Going on a Night Out’: Time Out, Transgression and Control - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As the previous chapter has highlighted, alcohol consumption plays an important role in the maintenance of friendships and in the individual and collective production of ‘girly’ or feminine identities in the NTE. Yet long-standing and pervasive images of alcohol consumption as a threat to femininity mean women’s negotiations of drinking continue to be fraught with tensions and ambivalences. In something of a paradox, ‘the contradictions engendered by post-feminist discourse constitute drunkenness as unfeminine, [yet] young women are enthusiastically exhorted to consume within the neoliberal culture of intoxication’ (Hutton et al. 2016: 82). In other words, to be a good, neoliberal citizen within leisure sites such as the NTE requires women to consume alcohol, yet the demands of femininity necessitate that they also show restraint. At the same time, the NTE is portrayed as a site where abandonment, hedonism and ‘rowdy’ behaviour are to an extent normalised, perhaps even encouraged, yet such behaviour ruptures traditional expectations of femininity as passive and ‘ladylike’. How do women negotiate and make sense of some of these tensions as they confront the ‘orderly disorder’ (Smith 2014: 2) of a typical night out? Is there a degree of acceptance of ‘rowdy’ or transgressive behaviour? And how does this sit alongside an expectation to be girly, as outlined in the previous chapter?
Keywords: Drinking Practices; Drunk Woman; Girly Girl; Kirsty; Transgressive Behavior

‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing

intersectionnalité - Office québécois de la langue française (Grand dictionnaire terminologique, 2019)
Cumul de différentes formes de domination ou de discrimination vécues par une personne, fondées notamment sur sa race, son sexe, son âge, sa religion, son orientation sexuelle, sa classe sociale ou ses capacités physiques, qui entraîne une augmentation des préjudices subis.
Keywords: Bibliographie; Nettoyer

Victim Services - ReadtheCode (2019)
Keywords: Nettoyer; À ajouter

Double Binds and Punchlines: An Examination of Women in Stand Up Comedy and Television Writers' Rooms - Sargent, Amberia (UCLA, 2019)
In this dissertation, I examine how double binds around sexuality and gender norms shape how women navigate sexual harassment and threats to their professional identities in stand up comedy and television writers’ rooms. I explain the ways the workplace dilemmas women confront are informed by race, sexuality, physical attractiveness, tenure, and relationship status.
Keywords: Sophie-Anne

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Le respect de la dignité des femmes dévoilant une agression à caractère sexuel:perspectives d'intervenantes sociales et communautaires Montréalaises - Souffrant, Kharoll-Ann (Université McGill, 2019)
Keywords: Bibliographie; Nettoyer

Mesures de soutien et d’inclusion des personnes trans et des personnes non binaires en milieu de travail : Guide pour les employeurs et les syndicats - Table nationale de lutte contre l'homophobie et la transphobie des réseaux de l'éducation (2019)
Keywords: Bibliographie; Nettoyer

Comment aider un·e ami·e qui a eu des comportements abusifs par le passé (et qui a changé depuis) ? - Thom, Kai Cheng (Nous faire justice : Reader sur le viol et les ripostes extra-pénales, 2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

La fabrique du viol - Zaccour, Suzanne (Leméac Éditeur, 2019)

Situation des femmes dans les industries artistiques et culturelles au Canada : Examen de la recherche (Hill Strategies Research Inc, 2018)
Cet examen recense plus de 250 rapports, articles et documents de sources ontariennes ou canadiennes contenant des données sur les femmes dans six secteurs d’activités artistiques et culturelles : les arts visuels, la danse, le théâtre, la littérature, la musique et les arts médiatiques/sur écran. Une de ses principales constatations est qu’il n’existe pas d’études ayant […]

#moiaussi de l’humour : un an après ? - Paré, Christelle (Le Journal de Québec, 2018)
Le #moiaussi en humour a sonné l'alarme, chiffres à l'appui.

Men's Intrusion, Women's Embodiment: A critical analysis of street harassment - Vera-Gray, F. (Routledge, 2018)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.

Un an depuis #moiaussi: la contestation dans les oeuvres - CÔTÉ, ÉMILIE (La Presse, 2018)
Le mouvement #moiaussi a inspiré auteurs, artistes et créateurs de toutes les disciplines artistiques. Tour d'horizon.

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Keywords: Irina

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

Écrire le viol (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou

Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? (Le Devoir, 2018)
La représentation gratuite du viol n’est pas sans effet chez les lectrices.

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

Le #metoo de Coeur de pirate - Cassivi, Marc (La Presse, 2018)
Béatrice Martin, alias Coeur de pirate, fera paraître vendredi son quatrième album, En cas de tempête, ce jardin sera fermé, un hommage à Paris qui coïncide avec ses 10 ans de carrière. Une très belle collection de textes sombres et poétiques, sur des musiques lumineuses et entraînantes, où l'auteure-compositrice-interprète évoque des épisodes douloureux de son passé.

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Keywords: Irina

Les humoristes font leur part pour #MoiAussi - Gendron-Martin, Raphaël (Le Journal de Montréal, 2018)
«On aurait pu avoir 40 humoristes dans le spectacle», lance le coanimateur de la soirée, Patrick Groulx.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

A Dance with Many Secrets: The Experience of Emotional Harm from the Perspective of Past Professional Female Ballet Dancers in Canada - Moola, Fiona; Krahn, Alixandra (Journal of Aggression, Maltreatment & Trauma, 2018)
Originating in the Italian and French courts, ballet is an age-old art that fuses aesthetics and athleticism (Wulff, 2008). Despite changing times, ballet masters and mistresses tenaciously hold on to a sense of deep traditionalism. However, some scholars suggest that unwavering devotion to the art may conceal troubled embodied relations and oppressive practices (Gvion, 2008). In this study, we drew on the phenomenological research tradition in an effort to further examine the power relations that play out on the body in the world of Canadian professional ballet (Papaefstathiou, Rhind, & Brakenridge, 2013). Twenty past professional female ballet dancers from across Canada participated in this study. Our dedicated dancers were relentless. They sacrificed body and mind in the pursuit of excellence in a broader cultural context that expected nothing less. The dancers normalized harmful emotional experiences, inappropriate sexual transgressions, and chronic injury (Gvion, 2008). They also described experiences of neglect—and feeling replaceable—after the onset of injury. We have attempted to theorize our findings within the context of embodiment literature and the work of gender theorists. Emboldened by our dancers’ voices, we have shed light—and broken secrets—regarding some of the harmful practices that still characterize professional ballet in Canada. We hope that our work might further continue efforts to democratize power imbalances in professional ballet and ultimately enhance holistic dancer development and health.

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Pantalacci, Sandrine (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]

Winnipeg comedy club bans discrimination, hatefulness, harassment | CBC News - Gibson, Shane (CBC, 2018)
Wee Johnny’s comedy room posted a sign this week warning that anyone violating a new anti-harassment policy — which bans “sexism, racism, homophobia, transphobia, physical intimidation or any other form of abusive behaviour” — may be asked to leave the club.

L'Université de Montréal fait son mea culpa (La Presse+, 2018)
L’Université de Montréal reconnaît avoir toléré, faute de balises adéquates, des comportements « inacceptables » du professeur Jean Larose, parti à la retraite en 2011 à la suite d’une plainte pour attouchements et harcèlement sexuels qui a été rejetée. Un cas

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Keywords: Bibliographie; Nettoyer

Charte égalité Hommes-Femmes - Centre national des arts du cirque (2018)
Keywords: Sophie-Anne

The Right of One's Own Image in the Recent Cases of Sexual Harassment in Film Industry: Applying the European Theory of Concentric Circles to Celebrities (In Particular, Women) - Corredoira, Loreto (Journal of Information Policy, 2018)
Keywords: Irina

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Keywords: Bibliographie; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

The Bystander Moment - Jeremy Earp (Media Education Foundation, 2018)
Keywords: Coffre à outils; À ajouter

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (Adult Education Research Conference, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (Lecture delivered at Utah State University, 2018)
Keywords: Bibliographie; Nettoyer

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.

L’ordinaire de la violence. Un cas d’atteinte sexuelle sur mineure en milieu artistique - Trachman, Mathieu (Travail, genre et sociétés, 2018)
L’ordinaire est un thème souvent mobilisé dans les études sur les violences de genre. À partir d’un cas d’atteinte sexuelle sur mineure, cet article a pour objectif d’en préciser les enjeux. Il montre en premier lieu que la notion d’ordinaire, qui signifie souvent ce qui est commun à toutes les femmes, gagne à voir son périmètre précisé : dans le cas analysé, le travail artistique, sa dimension vocationnelle, la personnalisation des relations entre professeur et étudiante, les coûts d’entrée dans le métier pour les femmes sont des éléments déterminants. Dans les études féministes, l’ordinaire désigne également les faits de violence qui caractérisent la vie quotidienne des femmes. En distinguant faits, situation et qualification, l’article montre que la qualification de violence implique un sentiment d’anormalité et une réflexivité largement absents dans les situations de violence de genre. Ce hiatus explique l’incertitude souvent inhérente à la qualification de violence et le caractère rétrospectivement énigmatique des situations de violence. L’ordinaire de la violence désigne ainsi moins une évidence occultée qu’un registre de l’expérience où les abus et les agressions sont intégrés dans le cours des choses et normalisés par les protagonistes.

Gender in the Music Industry: Rock, Discourse and Girl Power - Leonard, Marion (Routledge, 2017)
Why, despite the number of high profile female rock musicians, does rock continue to be understood as masculine? Why is rock generally assumed to be created and performed by men? Marion Leonard explores different representations of masculinity offered by, and performed through, rock music, and examines how female rock performers negotiate this gendering of rock as masculine. A major concern of the book is not specifically with men or with women performing rock, but with how notions of gender affect the everyday experiences of all rock musicians within the context of the music industry. Leonard addresses core issues relating to gender, rock and the music industry through a case study of 'female-centred' bands from the UK and US performing so called 'indie rock' from the 1990s to the present day. Using original interview material with both amateur and internationally renowned musicians, the book further addresses the fact that the voices of musicians have often been absent from music industry studies. Leonard's central aim is to progress from feminist scholarship that has documented and explored the experience of female musicians, to presenting an analytic discussion of gender and the music industry. In this way, the book engages directly with a number of under-researched areas: the impact of gender on the everyday life of performing musicians; gendered attitudes in music journalism, promotion and production; the responses and strategies developed by female performers; the feminist network riot grrrl and the succession of international festivals it inspired under the name of Ladyfest.

Rape and abuse: The music industry's dark side exposed (BBC News, 2017)
"Dangerous men" at the top of the industry are abusing their power, the BBC has been told.

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Keywords: Myriam; Résistance aux VACS

Not So Funny Business: Sexual Harassment in Stand-Up Comedy - Hansen, Briana (Workandmoney, 2017)
Up-and-coming Los Angeles comedian reflects on her experience of assault among some of the funniest people on the planet
Keywords: Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

2192 women in the Swedish music industry behind appeal against sexism (Dagens Nyheter, 2017)
Sexual assault. Rude and outspoken sexism.

L'Union des artistes dépose des griefs pour harcèlement - Radio-Canada (Radio-Canada, 2017)
Après une vague de dénonciations de gestes à caractère sexuel dans le milieu artistique, l'Union des artistes (UDA) annonce avoir déposé des griefs pour harcèlement.
Keywords: Bibliographie; Nettoyer

Forty-Seven DJs, Four Women: Meritocracy, Talent, and Postfeminist Politics - Gadir, Tami (Dancecult, 2017)
In 2016, only four of forty-seven DJs booked for Musikkfest, a festival in Oslo, Norway, were women. Following this, a local DJ published an objection to this imbalance in a local arts and entertainment magazine. Her editorial provoked booking agents to defend their position on the grounds that they prioritise skill and talent when booking DJs, and by implication, that they do not prioritise equality. The booking agents’ responses, on social media and in interviews I conducted, highlight their perpetuation of a status quo in dance music cultures where men disproportionately dominate the role of DJing. Labour laws do not align with this cultural attitude: gender equality legislation in Norway’s recent history contrasts the postfeminist attitudes expressed by dance music’s cultural intermediaries such as DJs and booking agents. The Musikkfest case ultimately shows that gender politics in dance music cultures do not necessarily correspond to dance music’s historical associations with egalitarianism.

Un nouveau festival d'humour pour rire encore un peu, beaucoup, ensemble - Baillargeon, Stéphane (Le Devoir, 2017)
Un regroupement d’humoristes comprenant plusieurs têtes d’affiche du Québec crée le Festival du rire de Montréal. La première mouture du nouvel événement prendra l’affiche à l’été 2018, promettent les artistes.

Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

Léa Clermont-Dion accuse Michel Venne de l’avoir agressée - Bussières, Ian; Piedboeuf, Guillaume (Le Soleil, 2017)
L’écrivaine et militante Léa Clermont-Dion, qui avait révélé en 2014 avoir été agressée sexuellement à l’âge de 17 ans, a déposé une plainte à la police contre le fondateur de l’Institut du Nouveau Monde, Michel Venne. Des allégations d’agression sexuelle que nie ce dernier.
Keywords: Bibliographie; Nettoyer

Michel Brûlé visé par une plainte d'agression sexuelle à Québec - Piedboeuf, Guillaume (La Tribune, 2017)
Une écrivaine de la Rive-Sud de Québec accuse l’éditeur Michel Brûlé de l’avoir agressée sexuellement à sa résidence du Vieux-Québec, en mars 2014, alors qu’elle venait lui proposer un manuscrit. Jill Côté a porté plainte à la police de Québec, vendredi, pour un incident dont M. Brûlé nie l’existence.
Keywords: Bibliographie; Nettoyer

Le patron des Éditions des Intouchables Michel Brûlé à son tour visé par des allégations d’inconduites sexuelles - Lévesque, Ève (Le Journal de Montréal, 2017)
Sept ex-employées se vident le cœur.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.

Inconduites sexuelles reprochées à Éric Salvail - Gagnon, Katia; Vallet, Stéphanie (La Presse, 2017)
Avances sexuelles en string, parties intimes exhibées ou empoignées, tentatives de séduction insistantes dans des salles de montage: 11 personnes ont raconté à La Presse avoir subi des inconduites, ou en avoir été témoins, de la part du producteur et animateur Éric Salvail, la plupart du temps dans un contexte professionnel.
Keywords: Bibliographie; Nettoyer

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.

Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

Architects singer calls out man who sexually assaulted a fan: 'Not at my f***ing show' (The Independent, 2017)
Singer paused the show after witnessing the incident from the stage

Swedish music festival to go 'women-only' following string of sexual assaults - White, Adam (The Telegraph, 2017)
Sweden's biggest music festival will be replaced next year by a women-only alternative after reports of a series of rapes and sexual assaults at this year's event.
Keywords: Crime; Culture; Music; Skepta; Standard; Sweden

Data and responsibility: Towards a feminist methodology for producing historical data on women in the contemporary UK film industry - Cobb, Shelley; Wreyford, Natalie (Feminist Media Histories, 2017)
This paper addresses how feminist interrogations of research methods and knowledge claims have an important role to play in the collection and dispersion of quantitative data. Taking the contemporary film industry as a historical formation, and seeking to identify and understand patterns of continued gendered inequality, we consider the methodological and ethical dilemmas we have experienced as feminist researchers gathering and presenting quantitative data on the numbers of women working in the UK film industry between 2003 and 2015. We argue that data plays a paradoxical role in creating a sense of women’s absence and arrive at a set of guiding principles for feminist quantitative research in film histories.

Des musiciennes unies contre le sexisme - Lauzon, Véronique (La Presse, 2017)
Cent trente-cinq femmes issues du milieu musical ont décidé de dénoncer le sexisme et les injustices qu'elles subissent régulièrement au travail.
Keywords: Bibliographie; Nettoyer

Code of Silence (The Dance Current, 2017)
Fifteen years ago, Lisa, a dance conservatory student, became pregnant. She was told in no uncertain terms by her school’s directors that abortion was recommended, and that she wouldn’t be allowed to continue attending the conservatory otherwise. It was made clear to her that the fact that her pregnancy would be in its seventh month at the time of graduation...

Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Keywords: Myriam; journalism

L'écrivain jeunesse Maxime Roussy en prison pour 5 ans - Nguyen, Michael (Le Journal de Montréal, 2017)
Pendant cinq ans, de 2006 à 2011, Roussy avait profité d’une jeune lectrice pour assouvir ses fantasmes sadomasochistes.
Keywords: Bibliographie; Nettoyer

The deterrent effects of Australian street-level drug law enforcement on illicit drug offending at outdoor music festivals - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne; Ritter, Alison; Weatherburn, Don; MacCoun, Robert (International Journal of Drug Policy, 2017)
Background Australian and international street-level drug law enforcement deploy many strategies in efforts to prevent or deter illicit drug offending. Limited evidence of deterrence exists. This study assessed the likely impacts of four Australian policing strategies on the incidence and nature of drug use and supply at a common policing target: outdoor music festivals. Methods A purpose-built national online survey (the Drug Policing Survey) was constructed using five hypothetical experimental vignettes that took into account four policing strategies (High Visibility Policing, Riot Policing, Collaborative Policing, and policing with Drug Detection Dogs) and a counter-factual (no police presence). The survey was administered in late 2015 to 2115 people who regularly attend festivals. Participants were block-randomised to receive two vignettes and asked under each whether they would use, possess, purchase, give or sell illicit drugs. Results Compared to ‘no police presence’, any police presence led to a 4.6% point reduction in engagement in overall illicit drug offending: reducing in particular willingness to possess or carry drugs into a festival. However, it had minimal or counterproductive impacts on purchasing and supply. For example, given police presence, purchasing of drugs increased significantly within festival grounds. Offending impacts varied between the four policing strategies: Drug Detection Dogs most reduced drug possession but High Visibility Policing most reduced overall drug offending including supply. Multivariate logistic regression showed police presence was not the most significant predictor of offending decisions at festivals. ConclusionConclusion The findings suggest that street-level policing may deter some forms of drug offending at music festivals, but that most impacts will be small. Moreover, it may encourage some perverse impacts such as drug consumers opting to buy drugs within festival grounds rather than carry in their own. We use our findings to highlight trade-offs between the goals of public health promotion and crime control in street-level enforcement.
Keywords: Deterrence; Drug law enforcement; Supply; Use

Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of Gender Studies, 2017)
Introduction to Special Issue of Journal of Gender Studies entitled Rape culture, lad culture and everyday sexism: Researching, conceptualizing and politicizing new mediations of gender and sexual violence.

Skipping a beat: Assessing the state of gender equality in the Australian music industry - Cooper, Rae; Coles, Amanda; Hanna-Osborne, Sally (2017)
This report demonstrates that male advantage is a pervasive feature of the Australian music industry. Using publicly available published data the report interrogates the industry dynamics that have produced a contemporary music scene in which radio playlists, festival line-ups, industry awards, peak bodies and major industry boards are dominated by male contributions and voices. We make 5 key recommendations, discussed in more detail in the report, to begin the process of addressing the industry’s chronic gender inequality: 1. Collect more and better data on the music industry on a gender disaggregated basis; 2. Establish a well-resourced independent gender equality industry advocacy body; 3. Use gender equality criteria in deciding public funding outcomes; 4. Increase women’s representation in decision-making structures; 5. Address gender bias in the Australian music industry by prioritising inclusivity and representation as core industry values (for example through funding and implementing training programs). The music industry is skipping a beat when it comes to gender equality. We hope that our report will stimulate industry thinking and action for change.

The Going Out In Sydney App: Evaluating the Utility of a Smartphone App for Monitoring Real-World Illicit Drug Use and Police Encounters Among Festival and Club Goers - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne Louisa (Substance Abuse: Research and Treatment, 2017)
Gaining accurate information on illicit drug use and policing in real-world settings is a challenge. This study examines the utility of a smartphone app (‘Going Out In Sydney’) to prospectively follow up illicit drug use and policing encounters at music festivals and licensed entertainment precincts in Sydney, Australia. In all, 38 regular festival and licensed entertainment venue attendees used the app to log nights out over a 3-month period, including (1) where they went (eg, festival, nightclub), (2) the prevalence of illicit drug use, and (3) the incidence and nature of police encounters. A survey and interview were then conducted about the utility of the app. The app enabled rich data collection (n = 353 entries) about illicit drug use and policing at both target settings. Follow-up surveys indicated that most participants were extremely satisfied with the ease of use of the app and privacy afforded, and compared with other data collection modes, such as paper-based logs and online surveys, rated the app the most desirable method of data collection. This suggests smartphone apps may be a viable option for future studies on illicit drug use and policing of drugs.
Keywords: Mobile app; app; drug use; offending; policing; smartphone

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Keywords: Bibliographie; Nettoyer

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, S (International Journal of Cultural Policy, 2017)

Consultations publiques sur le harcèlement et la violence sexuelle en milieu de travail: ce que nous avons entendu - Emploi et Développpement social Canada (Gouvernement du Canada, 2017)
Keywords: Bibliographie; Nettoyer

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Code of Silence: A call to action to address and prevent abuse in dance communities - Forcier, Marie France (The Dance Current, 2017)
Keywords: Bibliographie; Nettoyer

*Loi visant à prévenir et à combattre les violences à caractère sexuel dans les établissements d’enseignement supérieur - Gouvernement du Québec (RLRQ c P-22.1, 2017)
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments' policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands' creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors influenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-specific research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Debranchée (Unplugged) - Laurier, Mathilde; St-Laurent, Marie-Claude; Hébert, Maude; Milot, Marie-Ève (2017)
Débranchée (Unplugged) est une fiction qui traite des violences sexuelles dans le monde adolescent. La pièce raconte l'histoire de deux amies ébranlées par les rumeurs d'agressions sexuelles qui se propagent à haute vitesse dans leur école. Quand Allison brise la loi du silence, toute une chaîne de réactions s'enclenche. Des témoignages fusent, donnant une voix à toutes ces violences sexuelles trop souvent vécues dans l'anonymat. Devant l'ampleur du phénomène, les deux protagonistes cherchent à transformer l'explosion créée en un élan de solidarité. Elles iront jusqu'au bout. Le show aura lieu.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

"They're Only Laughing 'Cause You're Pretty": Women's Experiences at Comedy Clubs - Lopez, Victoria Angelina (2017)
Stand-up comedy, like many forms of public entertainment or workplace organizations, is a field dominated by men. The deeply embedded perception that women are not funny, or not as funny as their counterparts, allow men’s privileged position in pursuing their career in comedy without their humor being questions based on their gender. However, the women’s’ experiences were found to be challenging with women’s humor being questioned and overshadowed by a hostile environment of sexual harassment. This disparity in the number of women represented in comedy is even more prevalent when it comes to the number of women who participate in stand-up comedy at the amateur level of open mic nights. This thesis examines gender disparity among comedians, the prejudices and discrimination women comedians face at the level of amateur comedian, and how they navigate through those barriers in comedy. Based on the findings from 14 in depth-interviews with 7 men and 7 women comedians, as well as observations of open-mic nights, this study investigates their experiences and perceptions of gender politics in comedy.
Keywords: Comedy clubs; Communication and the arts; Social sciences; Sophie-Anne

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Le traitement médiatique du mouvement #AgressionNonDénoncée dans la presse écrite québécoise francophone - Savard-Moisan, Raphaëlle (Université du Québec à Montréal, 2017)
Keywords: Bibliographie; Nettoyer

Brit awards announce voting shakeup after #BritsSoWhite outrage (the Guardian, 2016)
Organisers say academy is more gender-balanced and diverse after last year’s failure to nominate black artists

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

« Sous la ceinture, unies pour vaincre la culture du viol », un livre qui tombe à point - Radio-Canada (Radio-Canada, 2016)
Judith Lussier, l'une des auteurs du livre « Sous la ceinture, unis pour vaincre la culture du viol », souligne que ce phénomène est omniprésent et tend à banaliser les gestes des agresseurs.
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

How to be a boss woman in the music industry - Jones, Rhian (Medium, 2016)
The music industry is hugely homogenised. In the UK, all three heads of the major record labels are men, and there’s just three women…

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

Drugs at the campsite: Socio-spatial relations and drug use at music festivals - Dilkes-Frayne, Ella (International Journal of Drug Policy, 2016)
Background Music festivals have received relatively little research attention despite being key sites for alcohol and drug use among young people internationally. Research into music festivals and the social contexts of drug use more generally, has tended to focus on social and cultural processes without sufficient regard for the mediating role of space and spatial processes. Methods Adopting a relational approach to space and the social, from Actor-Network Theory and human geography, I examine how socio-spatial relations are generated in campsites at multiple-day music festivals. The data are drawn from ethnographic observations at music festivals around Melbourne, Australia; interviews with 18–23 year olds; and participant-written diaries. Results Through the analysis, the campsite is revealed as a space in process, the making of which is bound up in how drug use unfolds. Campsite relations mediate the formation of drug knowledge and norms, informal harm reduction practices, access to and exchange of drugs, and rest and recovery following drug use. Conclusions Greater attendance to socio-spatial relations affords new insights regarding how festival spaces and their social effects are generated, and how they give rise to particular drug use practices. These findings also point to how festival harm reduction strategies might be enhanced through the promotion of enabling socio-spatial relations.
Keywords: Drug use; Enabling places; Ethnography, Music festivals; Social context; Socio-spatial relations

Nightlife Ethnography, Violence, Policing and Security - Tomsen, Stephen; Wadds, Phillip (2016)

Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Keywords: audience research; cultural value; live music; music policy; regulation

How can the music industry tackle its diversity issues? (Music Business Worldwide, 2016)
Kieron Faller from CI reveals best-practice for diverse businesses…

LGBT People and the UK Cultural Sector: The Response of Libraries, Museums, Archives and Heritage since 1950 - Vincent, John (Routledge, 2016)
This book examines the complex and conflicting relationships between LGBT people and our cultural and heritage organisations including libraries, museums and
Keywords: Bibliographie; Nettoyer

Taking time between g-string changes to educate ourselves: Sinéad O’Connor, Miley Cyrus, and celebrity feminism - Brady, Anita (Feminist Media Studies, 2016)
This article examines the feminist response to a 2013 online “feud” between singers Miley Cyrus and Sinéad O’Connor that began when Cyrus connected the video for her single “Wrecking Ball” to O’Connor’s video for “Nothing Compares 2 U.” O’Connor’s response criticised Cyrus’ sexualised image, and the exchanges that followed sparked debate among feminists over the limits of sexual “agency,” and the sexual politics of feminism. This took place within a wider media context that has seen an apparent increase in female celebrities explicitly identifying themselves as feminist. Critics of this “celebrity feminism” argue that the sexualised star systems of its proponents are at odds with the aims of feminist politics. This article draws on post-structuralist feminist theory to question the positioning of celebrity feminism as exterior to an imagined “feminist movement.” Using the Cyrus/O’Connor feud, I argue that such a binary potentially reaffirms the structures of power that feminism seeks to oppose, and ignores the ways celebrity culture and contemporary media practice might combine to produce new understandings of the field of feminism.
Keywords: Celebrity feminism; Miley Cyrus; Sinéad O’Connor; feminist post-structuralism; third-wave feminism

Damaging and daunting: female journalists’ experiences of sexual harassment in the newsroom - North, Louise (Feminist Media Studies, 2016)
Female journalists’ experiences of sexual harassment are barely documented in the literature about Australian news journalism despite evidence of its ongoing prevalence. There have been some stories of harassment detailed in autobiographies by female journalists and the occasional article in the mainstream media about individual incidents, but it wasn’t until 1996 that a union survey provided statistical evidence of an industry-wide problem. That Media, Entertainment and Arts Alliance survey found that more than half of the 368 female participants had experienced sexual harassment at work. In 2012, I conducted the largest survey of female journalists in Australia finding that there was an increased number of respondents who had experienced sexual harassment in their workplaces. In a bid to better understand female journalists’ experiences of sexual harassment, this paper analyses written comments made by survey participants in relation to key questions about harassment. It finds that most downplay its seriousness and do not make formal reports because they fear victimisation or retaliation. As a consequence, a culture of secrecy hides a major industry problem where many women believe they should work it out themselves and that harassment is the price they have to pay for working in a male-dominated industry.
Keywords: Myriam; Sexual harassment; female journalists; gender and work; gendered newsrooms; survey of Australian female journalists

Risky Pleasures?: Club Cultures and Feminine Identities - Hutton, Fiona (Routledge, 2016)
In this book Fiona Hutton provides a fascinating insight into women's experiences of clubbing. Based on a rich ethnographic account of the Manchester club scene, Risky Pleasures? is set within the context of the theoretical literature on youth subcultures, female friendship, consumption, risk and the city. The work highlights both the producers of club scenes - promoters, DJs, dealers - and the consumers - women negotiating pleasure and risk in club spaces and in the city at night. It explores the range of club spaces, developing a typology of 'mainstream' and 'underground' clubs, and considers how different types of participants are attracted to different 'scenes'. It examines women's recreational drug-use within a club context and discusses issues of sexuality, tolerance and the importance of 'attitude' in terms of women's feelings of safety. Revealing the important role of different spaces and different atmospheres in how women participate in club scenes, Fiona Hutton argues that drug taking and sexual pleasure are always contextualized within the environments created in different spaces, and that the risk and danger negotiated by women clubbers are counterbalanced by fun and pleasure - and ultimately empowerment.

Jian Ghomeshi est acquitté - Radio-Canada (Radio-Canada, 2016)
Jian Ghomeshi est acquitté de toutes les accusations qui pesaient contre lui. Le juge William B. Horkins a rendu sa décision, jeudi matin, à Toronto.
Keywords: Bibliographie; Nettoyer

Challenging the Myth of Gender Equality in Sweden - Lena, Martinsson; Gabriele, Griffin (Policy Press, 2016)
Sweden is often considered one of the most gender-equal countries in the world and held up as a model to follow, but the reality is more complex. This is the first book to explode the myth of Swedish gender equality, both offering a new perspective for an international audience, and suggesting how equality might be rethought more generally. While the authors argue that the gender-equality mantra in Sweden has led to a society with increased opportunities for some, they also assert that the dominant norm of gender equality has become nationalistic and builds upon heteronormative and racial principles. Examining the changing meanings and parameters of gender equality against the country's social-democratic tradition and in the light of contemporary neoliberal ideologies, the book constitutes an urgent contribution to the debates about gender-equality policies and politics.
Keywords: Social Science / Gender Studies; Social Science / Sociology / General

Women Harassment at Workplace: A Study of Pakistani Television Channels - Zia, Anjum; Batool, Sumera; Yasin, Zaeem (2016)
The present study explores the contemporary status of women harassment in Pakistani media industry taking alongside theoretical consideration of liberal feminism theory. An empirical method was adopted and in-depth interviews were conducted with media employees of both genders at television channels of the country. The study examined six core dimensions of harassment including working environment of the organization, male dominance, women harassment at workplaces, stereotype thinking patterns about women, offensive remarks on appearance of female colleagues and reporting of harassment issues to explore the current situation of women harassment in television channels of high repute. Findings of the study revealed that regardless of their ample role in thriving Pakistani media, women journalists are facing harassment at their workplaces but majority of them lesser likely to report harassment issues. Existence of stereotype thinking patterns about women and offensive remarks about appearance of women point towards severity of situation about women harassment at Pakistani media industry. Interestingly, despite male domination in media industry, general environment of media organizations is reported as satisfactory at large, whereas research concludes with highlighting areas for people working within and outside media organizations to eradicate harassment at workplaces. Keywords: Women harassment, male dominance, stereotype thinking patterns, Pakistani media, reporting of harassment.
Keywords: Myriam; Television

Valuing Musical Participation - Pitts, Stephanie (Routledge, 2016)
Increasingly, it is becoming evident that those involved in socio-musical studies must focus their investigative lens on musical practice and articulation of the self, on music and community involvement and on music as a social medium for social relationships. What motivates people to be involved in musical performance, and how do they articulate these needs and drives? What do performers gain from their involvement in musical activities? How do audience members perceive their relationship to the performer, the music and the event? These questions and many more are addressed here with the benefit of detailed empirical work, including case studies of a chamber music festival and a contemporary music summer school. Pitts investigates the value of musical participation for performers and audience members in a range of contexts, using a multi-disciplinary approach to place new empirical data in the framework of existing theory and literature. Themes examined include: the shared musical experience; the social structures of performing societies; how people identify with music; the values implicit in musical preferences; the social responsibilities of the performer; the audience view of concerts and festivals; the social power of music and educational implications and responsibilities. Pitts draws upon literature from musicology, sociology and psychology of music, ethnomusicology, music education and community music to demonstrate the diversity of enquiry about musical behaviours. The conclusions of the book are based upon empirical evidence gleaned through case studies, with the data integrated thematically throughout, to enable a greater depth of discussion than individual studies usually permit.

Who are the most powerful people in music? Jay Z? Kanye? Beyoncé? No, it’s old white men (the Guardian, 2016)
The 2016 Billboard Power 100 is dominated by white men born before Elvis had a hit. This isn’t only a problem of representation – it’s also bad for the industry

Learning to labour unequally: Understanding the relationship between cultural production, cultural consumption and inequality - Oakley, Kate; O'Brien, Dave (Social Identities, 2016)
Inequality has become essential to understanding contemporary society and is at the forefront of media, political and practice discussions of the future of the arts, particularly in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The article considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The paper argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy, despite the importance of culture to British and thus international policy agendas. The article uses the example of higher education in the UK to think through the relationship between cultural consumption and production. In doing, so the article maps out a productive possibility for a new research agenda, by sketching where and how research might link cultural consumption and production to better understand inequality.

Centre de Ressources et d'intervention pour homme (Criphase, 2016)
Keywords: Coffre à outils; À ajouter

Ressources d’aide (Fondation Marie-Vincent, 2016)
La Fondation Marie-Vincent aide les enfants et les adolescent·e·s victimes de violence. Elle contribue à prévenir la violence sexuelle.
Keywords: Coffre à outils; À ajouter

Navigating the boys’ club: Debra DiGiovanni and the performative strategy of comic self-deprecation - Deveau, Danielle Jeanine (International Journal of Cultural Studies, 2016)
This article considers Canadian comedian Debra DiGiovanni’s self-deprecatory humour as a performative strategy. In keeping with a performance tradition of self-deprecation as established by women like Phyllis Diller and Joan Rivers, DiGiovanni offers ‘failure’ as a comic strategy. Her comedy is heavily reliant upon the framing of her lack in relationships, in self-control and in body image (in relation to normative gender standards and expectations). At the same time, however, DiGiovanni also engages critically with gendered expectations of heteronormative desirability, lampooning thin women, superficial men and celebrity culture. Although her comedy is generally characterized by self-deprecation, her humour also leaves space for an ambivalent politics of gender.
Keywords: Sophie-Anne

Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music

Metal and Sexism - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 6 considers the allegations that hard rock and metal is sexist. Talking to British women fans reveals that in their experiences, hard rock and metal is less sexist than the ‘mainstream’. Using research on sexism across a range of fields, Hill argues that understanding what counts as sexism is complex and requires critical work by fans when sexism is normalised. Listening to what fans say about the context of their experiences within their broader lives is vital for better understanding. The author argues that the genre provides moments in which women fans may gain a feeling of genderlessness. Ultimately, however, the feeling of liberation only comes through assimilation into the culture, a culture that ignores women as much as possible. Nevertheless, that temporary feeling is a valuable one.
Keywords: Hard Rock; Metal Event; Music Video; Sexual Harassment; Unwanted Sexual Attention

The Gendered Experience of Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
The final chapter argues that close examination of the specific experiences of women in their engagements with the hard rock and metal media, the music, and musical events reveals how the experience of music is shaped by sexist assumptions about women and about how music should be listened to. Musical pleasure does not exist on a universal, transcendental plane. It is informed and shaped by the socio-cultural circumstances of the listener. Hill maintains that it is vital to acknowledge how these circumstances make for differing experiences: it is an important first step for countering sexism. The chapter concludes with a short plan for how hard rock and metal may imagine a genderless future, and how this imagined community might work towards it.
Keywords: Hard Rock; Metal Musician; Music Culture; Normative Femininity; Science Fiction

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community

Women Fans and the Myth of the Groupie - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 4 scrutinises the impact that the myth that women fans are groupies has on British hard rock and metal women fans. Women fans must negotiate the stereotype without accepting the title if they want their fandom to be respected, this results in a defensiveness about sexual and fannish reputations, which is an overtly gendered experience. Hill moves to examine the ways in which women’s desire for musicians and the complicated ways in which it must be negotiated impact on fans’ ability to express their fandom and their sexuality. The problem of the groupie myth lies not just with the expectations it places upon women but also in the ways in which it prevents discussion of more sensual and embodied experiences of musical pleasure.
Keywords: Hard Rock; Music Industry; Physical Attraction; Sexual Attraction; Sexual Pleasure

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël

Une victime de Claude Jutra témoigne: des attouchements dès 6 ans - Pilon-Larose, Hugo (La Presse, 2016)
Keywords: Bibliographie; Nettoyer

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

Unwanted Sexual Attention in Licensed Venues: Considering LGBTIQ Young Adults' Experiences and Perceptions - Fileborn, Bianca (2015)
English Abstract: Sexual violence within the lesbian, gay, bisexual, transgender/transsexual, intersex and queer (LGBTIQ) communities remains largely under-researched and under-theorised. Yet, emerging research suggests that sexual violence is a significant issue within the LGBTIQ communities. Additionally, the occurrence of sexual violence and unwanted sexual attention within specific social and cultural contexts is, for the most part, insufficiently examined. This article draws on research exploring young LGBTIQ adults’ perceptions and experiences of unwanted sexual attention in licensed venues. Firstly, I consider the theoretical and conceptual underpinnings of ‘unwanted sexual attention’ as a category of analysis. I then move on to consider participants’ use of licensed venues, the particular significance of pubs and clubs to LGBTIQ young people, and their perceptions and experiences of unwanted sexual attention. Finally, I discuss the implications of these findings for theoretical and conceptual understandings of unwanted sexual attention and sexual violence.
Keywords: Camille; Gender; Género; LGBTIQ; economía nocturna; licensed venues; locales con licencia; night time economy; orientación sexual; sexual orientation; sexual violence; violencia sexual

‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only

Victoria Sets Up Taskforce To Tackle Harassment Of Women At Gigs (Tone Deaf, 2015)
Following a meeting of the Victorian Live Music Roundtable yesterday, Victorian Minister for Consumer Affairs, Gaming and Liquor Regulation Jane Garrett

All the girls in town: The missing women of Australian rock, cultural memory and coverage of the death of Chrissy Amphlett - Strong, Catherine (Perfect Beat, 2015)
This article will use the cultural and media materials produced around the death of Chrissy Amphlett as a way of interrogating the fact that surprisingly few resources exist that document or commemorate the contribution of women to the rock music scene in Australia. As Amphlett is unusual in being a woman who has, even before her death, claimed a place in the Australian rock canon, examining materials that are designed to construct her legacy upon her passing will provide examples of how women in Australian rock are discussed. It will be demonstrated that Amphlett’s gender is central to these discussions, and that she is used to both obscure the contributions of other women performers and to deny a need for women musicians to even be an object of discussion at all. These indings will be analysed using Aleida Assmann’s concepts of functional and storage memory, and it will be argued that the lack of information that we have about past female rockers makes it harder for women in Australia to see this ield as one they can participate in, and also makes the retention of memories about currently successful women musicians less likely.

Pathways to Help: Adolescent Sexual Assault Victims’ Disclosure and Help-Seeking Experiences - Campbell, Rebecca; Greeson, Megan R.; Fehler-Cabral, Giannina; Kennedy, Angie C. (Violence Against Women, 2015)
In this study, we conducted semistructured interviews with N = 20 adolescent sexual assault victims who sought postassault help from the medical and legal system to understand young survivors’ disclosure and help-seeking processes. Results revealed three distinct disclosure patterns and pathways to help-seeking. First, in the voluntary disclosure group, victims told their friends, who encouraged them to tell an adult, who then encouraged—and assisted—the survivors in seeking help. Throughout this process, the survivors’ disclosures at each step were within their control and reflected their choices for how to proceed. Second, in the involuntary disclosure pattern, victims also first disclosed to friends, but then those friends told adults about the assault, against the survivors’ wishes; the adults made the victims seek help, which was also against the survivors’ preferences. Third, in situational disclosures, the survivors were unconscious at the time of the assault, and their friends disclosed and sought help on their behalf. We also examined how these initial disclosure patterns related to victims’ continued engagement with these systems.
Keywords: adolescents; disclosure; help-seeking; rape; sexual assault

‘I Think Women are Possibly Judged More Harshly with Comedy’: Women and British Television Comedy Production - Mills, Brett; Ralph, Sarah (Critical Studies in Television, 2015)
Critics and creative workers have recently highlighted the lack of women working in British television comedy. Through thematic analysis of interviews with British television comedy professionals, this article explores how women talk about their work and their position within the industry. Outlining the specific industrial contexts within which female comedy professionals work, the article examines institutionalised gender norms and practical impediments which the interviewees' responses reveal, while also exploring the institutional and personal initiatives which they have developed to address these problems.

Cultural Value and Inequality: A Critical Literature Review - Oakley, K; O'Brien, D (2015)
Inequality has become essential to understanding contemporary British society and is at the forefront of media, political and practice discussions of the future of the arts in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The literature review considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The review argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy. The review concentrates on the ‘big three’ issues of inequality – race, class and gender, where most of the literature is to be found, but also touches on disability, sexuality and spatial inequality. All of the research reviewed suggests an undeniable connection between cultural value and inequality. Understanding that connection is currently impeded by problems with data. The report suggests the political saliency of this topic means that public policy must do more to provide robust research, particularly about cultural production.

Sex, Gender and Work Segregation in the Cultural Industries - Hesmondhalgh, David; Baker, Sarah (The Sociological Review, 2015)
This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing on interviews, we claim that the following stereotypes or prevailing discourses, concerning the distinctive attributes of women and men, may influence such segregation: that women are more caring, supportive and nurturing; that women are better communicators; that women are ‘better organized’; and that men are more creative because they are less bound by rules.
Keywords: cultural industries; sexual division of labour; stereotypes; work segregation

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social

Le mouvement masculiniste au Québec. L'antiféminisme démasqué - Blais, Mélissa; Dupuis-Déri, Francis (Les Éditions du remue-ménage, 2015)

What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Keywords: Bibliographie; Nettoyer

The Economic and Cultural Value of Live Music in Australia 2014 - Carter, D. (2015)
The Economic and Cultural Value of Live Music in Australia 2014

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism

"for People Who Aren't Sure Who They Are, Theatre is a Great Place to Be": Narratives of Actors and their Sexual Identities - McCadden, Theodore Edward (Pennsylvania State University, 2015)
Keywords: Bibliographie; Nettoyer; Raphaël

Ghomeshi, l’avant et l’après - Deglise, Fabien (Le Devoir, 2014)
L’ex-animateur-vedette emporte aussi dans sa chute la loi du silence envers les abus sexuels.
Keywords: Bibliographie; Nettoyer

Unspeakable Inequalities: Post Feminism, Entrepreneurial Subjectivity, and the Repudiation of Sexism among Cultural Workers - Gill, Rosalind (Social Politics: International Studies in Gender, State & Society, 2014)
Work in the cultural and creative fields is marked by stark and growing inequalities relating to gender, class, and race/ethnicity. Yet, the same industries are also characterised by an ethos that celebrates openness, egalitarianism, and meritocracy. This paper explores this paradox, focusing in particular on gender inequalities. It argues that there is a need to move beyond the standard conventional explanations for women's under-representation within the creative workforce, which point to female childbearing and childcare as central. Whilst not disputing the significance of motherhood to women's career trajectories, the paper suggests that the repeated focus on maternity is problematic and may close down other areas of potential investigation and critique. The paper suggests that three alternative foci would repay attention in understanding inequalities in the CCI. First, the new, mobile, subtle, and revitalised forms of sexism in circulation urgently require further examination. Secondly, the power of the dominant post feminist sensibility which, in suggesting that “all the battles have been won,” renders inequality increasingly difficult to voice or speak about, demands critique. Thirdly, the new forms of labouring subjectivity required to survive in the field of cultural work may themselves be contributing to the inequalities in the field, by favouring an entrepreneurial individualistic mode that disavows structural power relations. These three aspects of life in the field of cultural work merit further attention and suggest that gender inequality has a variety of different causes, not all located in women's childbearing abilities. Moreover, the paper argues that the very myth of egalitarianism at work in the CCI may itself be a key mechanism through which inequality is reproduced.

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Guest, Carly (European Journal of Cultural and Political Sociology, 2014)

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Keywords: Bibliographie; Irina; Nettoyer

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Safe Space: Towards a Reconceptualization (Antipode, 2014)
The term “safe space” dates to the late twentieth century women's movement, but it has since been used in many different contexts. In this paper, we review and analyze historical and contemporary “safe spaces”. These include “separatist” safe spaces in women's, anti-racist, and feminist communities, “inclusive” safe space classrooms, and safe spaces in which (non-human) objects are central. We argue that safe spaces should be understood not through static and acontextual notions of “safe” or “unsafe”, but rather through the relational work of cultivating them. Such an understanding reveals several tendencies. Namely, safe spaces are inherently paradoxical. Cultivating them includes foregrounding social differences and binaries (safe–unsafe, inclusive–exclusive) as well as recognizing the porosity of such binaries. Renegotiating these binaries is necessarily incomplete; a safe space is never completely safe. Even so, we encourage the critical cultivation of safe space as a site for negotiating difference and challenging oppression.
Keywords: activism; intersectionality; paradoxical space; porosity; safe space; safety

Making Media Work: Cultures of Management in the Entertainment Industries - Johnson, Derek; Kompare, Derek; Santo, Avi (NYU Press, 2014)
In popular culture, management in the media industry is frequently understood as the work of network executives, studio developers, and market researchers-"the suits"-who oppose the more productive forces of creative talent and subject that labor to the inefficiencies and risk aversion of bureaucratic hierarchies. However, such portrayals belie the reality of how media management operates as a culture of shifting discourses, dispositions, and tactics that create meaning, generate value, and shape media work throughout each moment of production and consumption. Making Media Work aims to provide a deeper and more nuanced understanding of management within the entertainment industries. Drawing from work in critical sociology and cultural studies, the collection theorizes management as a pervasive, yet flexible set of principlesdrawn upon by a wide range of practitioners-artists, talent scouts, performers, directors, show runners, and more-in their ongoing efforts to articulate relationships and bridge potentially discordant forces within the media industries. The contributors interrogate managerial labor and identity, shine a light on how management understands its roles within cultural and creative contexts, and reconfigure the complex relationship between labor and managerial authority as productive rather than solely prohibitive. Engaging with primary evidence gathered through interviews, archives, and trade materials, the essays offer tremendous insight into how management is understood and performed within media industry contexts. The volume as a whole traces the changing roles of management both historically and in the contemporary moment within US and international contexts, and across a range of media forms, from film and television to video games and social media.

Putting gender in the mix: employment, participation, and role expectations in the music industries - LEONARD, MARION (The Routledge Companion to Media & Gender, 2014)
Eﬀorts to map women’s participation in the music industries have been hampered by a lack of data. However, available statistics point to a continuing underrepresentation of women in the music industries; and the disparity is particularly acute within certain areas of practice. In 2010 the Performing Rights Society for Music (PRS), the UK’s leading collection society, revealed that women accounted for only 14 percent of their registered music creators and writers. This statistic prompted the PRS Foundation to fund the “Women Make Music” initiative as a way to raise awareness of the gender gap, correct stereotypes, encourage participation, and increase the proﬁle of women creating new music. Research commissioned in 2008 by the Cultural Leadership Programme and publishedas a substantial report, found that in the UK music sector “only 20% of businesses have any form of female representation on the management team and only 10% have an all female team” (Cultural Leadership Programme 2008: 29). According to the report, women in the music sector were generally very underrepresented within positions of responsibility: the average number of female executives per ﬁrm was as low as 0.2. Such evidence of gender inequality in leadership positions within the music industries is by no means unique to the UK. In 2012 the editorial team of the Australasian Music Industry Directory (AMID), in consultation with other industry professionals, ranked for the ﬁrst time the most powerful people in the Australian music industry. The criteria included who has the greatest “ability to ‘shape’ the scene,” along with “their involvement in industry initiatives, overall career accomplishment, economic impact and public proﬁle” (Fitzsimons 2012). The “power list” included 50 places and 56 people (some business partners held joint positions). Only six women appeared on the list, two of whom shared their place with a male colleague; overall, then, women were just under 11 percent. While the list can be critiqued for its partiality, it indicates the music industries’ gender gap. Books on women working in the music industries usually focus on women musiciansand performers, often with the aim of celebrating women’s contribution to the history of popular music (see, for example, Dahl 1984; Gaar 1993; Hirshey 2001; Downes 2012). In documenting women’s experience, ﬁeld research with musicians has shownhow women have established their music careers, from acquiring instruments and learning to play, to performing and navigating the music business (see, e.g., Bayton 1998; Tucker 2000; Reddington 2007; Leonard 2007). A few speciﬁcally highlight women involved in music production and sound engineering (Sandstrom 2000; Smith 2009). Some recent work on women’s changing relationship with music technologies examines how artist-producers (Wolfe 2012) and women involved in the electronic dance music scene (Farrugia 2012) have navigated a gendered sphere of practice which has historically and discursively been associated with masculinity. Music journalism has also been a focus, with critical accounts addressing the work of women music journalists and the gendered discourse of music journalism (McDonnell 1995; Davies 2001; McLeod 2001). While the literature on women musicians, journalists, DJs, and music engineers is growing, the experience of women working in other roles within the music sector is much less well documented. Indeed, Smith (2009: 308) remarks that, except for musicianship, “scholarship on gender segregation in other music industry roles has been meagre. Because of this, the gendered division of labour in the music industry is not yet adequately understood.” This chapter explores how gendered attitudes circulate within the workplace andin what ways they frame work in diﬀerent sectors of the music industries. The plural term “music industries” suggests the chapter is not engaging with a uniﬁed ﬁeld of practice, nor is it concerned only with the recording industry (Williamson and Cloonan 2007). I will draw on interviews with eight women who have worked in artist management, tour management, A&R (artist and repertoire), and concert promotion, although ﬁrst I discuss the contexts in which these women work as a way to establish the extent to which their occupations can be broadly characterized as sex segregated. These women work in largely under-studied but particularly sex-segregated areasof music employment. All eight were based in London, England and ranged in levels of seniority from a booking agent’s assistant to a general manager of a record company. Many of the women had established portfolio careers, having worked in different roles, including radio promotion, international relations, music publishing, and marketing, so had diﬀerent levels of experience in management, A&R, and concert promotion. For example, one participant worked for two years at a junior level in A&R before moving on to develop expertise in other areas, eventually becoming a general manager of a record company. Another participant began as a regional A&R scout and was promoted to A&R manager, where she stayed ten years. Therefore, they could oﬀer a broad perspective: collectively they were engaged with international professional networks, international tour management, and the management and career development of artists building international proﬁles. The majority of them worked with rock bands and artists but some had worked with artists in other genres. The participants could also reﬂect on their experience of working with artists at diﬀerent stages of career development, from new and developing bands through to major international recording stars. Seven of the approximately hour-long interviews were conducted by telephone; their responses to the open-ended questions were recorded and transcribed. One respondent oﬀered a written response to the research questions via email. The women all seemed candid in their responses. Their comments have been anonymized; references to particular record labels, bands, or named individuals have been omitted.

A Music Room of One's Own: Discursive Constructions of Girls-only Spaces for Learning Popular Music - Björck, Cecilia (Girlhood Studies, 2013)
This article elaborates on discursive constructions of girls-only settings through the spatial metaphor of a room of one's own, as articulated in round-table discussions among staff and participants from girl-centered music programs in Sweden. The idea of a separate room refers to spaces for collective female empowerment as well as for individual knowledge acquisition and creativity. These spaces are constructed so as to provide the possibility for exploration, subjectivity, and focus, by offering (partial and temporary) escape from competition and control, from a gendered and gendering gaze, and from distraction. Girl-centered programs are also discussed as paradoxical because they function as gender-neutral when seen from the inside, but gender-specific when seen from the outside.

From victim to survivor - and from survivor to victim: Reconceptualising the survivor journey - Jordan, Jan (Sexual Abuse in Australia and New Zealand, 2013)
Being recognized as a rape survivor has often been interpreted as implying a linear progression from the negative state of victimisation, experienced in the presence of the offender, to a stronger, more positive state, typically facilitated by external support mechanisms. Drawing primarily on interviews conducted with women victimised by New Zealand serial rapist, Malcolm Rewa, this article challenges the concept of a journey 'from victim to survivor' by considering the multiple ways in which these women sought to protect themselves and survive during the attack while also experiencing aspects of their postattack involvement with individuals and agencies as further victimisation. The article concludes by outlining some initial implications regarding what this may mean for professionals working with victim/survivors of sexual violence.
Keywords: Bibliographie; Nettoyer

Safe Space: The Riot Grrrl Collection - Keenan, Elizabeth K.; Darms, Lisa (Archivaria, 2013)
Riot Grrrl, an early-1990s teen feminist movement, adopted punk’s DIY modes of expression to encourage girls to address their shared oppression. The Riot Grrrl Collection, held at New York University’s Fales Library & Special Collections, documents the movement through the personal papers of those who were active in its formative years. This article uses the lens of feminist “safe space” to look at the collection from two perspectives: that of its founder, Lisa Darms, who is senior archivist at Fales, and that of ethnomusicologist Elizabeth Keenan, a scholar who has worked extensively with the collection. The concept of safe space was crucial to the all-girl meetings, dance parties, and bands that formed the foundation of Riot Grrrl. The authors argue that the safe space of Riot Grrrl created an intimate counter-public – that is, a space where girls established a feminist community through shared texts – but one that sometimes worked against its own intentions: boundaries erected for safety sometimes led to exclusion along lines of race, class, or gender identity. The authors extend the idea of safe space to issues of collection building from and within activist communities; to ideas of intimacy and privacy as they play out for donors, for researchers, and in the special collections reading room; and to the tension between the desire for access to activist history versus the requirements of archival preservation. The article examines how iterations of safe space are enacted across the personal papers in the Riot Grrrl archive, through both the materials themselves and their place in the archive. RÉSUMÉ Riot Grrrl, un mouvement du début des années 1990 pour adolescentes féministes, s’est inspiré du mouvement punk pour adopter les modes d’expression du « Do it yourself (DIY) », dans le but d’encourager les adolescentes à aborder leur oppression commune. La collection Riot Grrrl, détenue par la Fales Library & Special Collections de l’University New York, documente le mouvement grâce aux documents personnels de celles qui en étaient actives durant ses premières années. Cet article se sert du concept féministe du « lieu sûr » (« safe space ») afin d’examiner la collection à partir de deux perspectives : celle de sa fondatrice, Lisa Darms, qui est archiviste supérieure à Fales, et celle de l’ethnomusicologue Elizabeth Keenan, une spécialiste qui a travaillé en profondeur avec cette collection. Le concept du lieu sûr était crucial pour les adolescentes lors de leurs réunions et soirées dansantes et pour leurs groupes musicaux qui ensemble ont contribué à la fondation de Riot Grrrl. Les auteurs soutiennent que le lieu sûr de Riot Grrrl a créé un « contre-public intime » – c’est-à-dire un espace dans lequel les adolescentes ont pu établir une communauté féministe par l’entremise de textes partagés – mais un contre-public qui opérait parfois contre ses propres intentions : les limites imposées pour délimiter le lieu sûr ont parfois mené vers des exclusions basées sur la race, les classes sociales ou l’identité de genre. Les auteures élargissent le concept du lieu sûr aux questions liées à la création de collections par des communautés militantes et dans ces milieux; aux idées de l’intimité et de la vie privée auxquelles sont confrontés les donateurs et les chercheurs dans la salle de lecture des collections spéciales; et à la tension entre le désir d’avoir accès à l’histoire militante et les besoins liés à la conservation archivistique. Cet article examine comment l’itération du lieu sûr se fait par rapport aux documents personnels des archives Riot Grrrl, tant du côté des documents eux-mêmes que de leur place dans les archives.

Female, Mosher, Transgressor: A 'Moshography' of Transgressive Practices within the Leeds Extreme Metal Scene - Riches, Gabrielle; Lashua, Brett; Spracklen, Karl (IASPM Journal, 2013)
This paper examines and reconceptualises transgression in the Leeds extreme metal music subculture through theories of performance, embodiment and spectacle. The spectacle, for Debord (1967), is a social relation that is alienating and mediated by images, visuals, and technology. At a live extreme metal concert fans subvert social norms, challenge gendered expectations, and disregard norms of etiquette and decency. Moshing is the most visible and sensuous example of transgression within the extreme metal scene. It is an aggressive, physically demanding performance which embodies resistance to the impersonal and disillusioning world of the spectacle (Halnon, 2004). The pit is a transgressive space that is itself transgressed by women who participate in this masculine, chaotic space, disrupting the homosocial bonds of male solidarity (Gruzelier, 2007). This paper offers an ethnographic account of a female metal fan participating in the transgressive practice of moshing within the Leeds metal music scene – a moshography.
Keywords: Moshpits; embodiment; extreme metal music; performance ethnography; spectacle; transgression

Why producers of music use discourses of consumption (and why we shouldn't think that makes them prosumers) - Cluley, Robert (Arts Marketing: An International Journal, 2013)
Purpose ‐ The purpose of this paper is to demonstrate how people making music represent their production activities using images of consumption. Design/methodology/approach ‐ Supporting evidence is based on in-depth interviews with musicians and support personnel. The data are structured through a thematic analysis. Findings ‐ The paper argues that consumption serves as a discursive resource that allows cultural producers to make sense of production activities which do not conform to an image of production as an alienated form of labour. Originality/value ‐ Relating the analysis to the ongoing attempts to conceptualise cultural producers through the concept of prosumption, the paper concludes that there are limits to cultural producers' abilities to represent their production activities as production rather than a structural change in social or economic organisation, as suggested by some consumer researchers.

Why unpaid interns are bad for the music industry (the Guardian, 2013)
Helienne Lindvall: Big US record labels are being sued by former interns who worked for free – how do their UK counterparts measure up?

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Q&A: Veteran Music Video Director Diane Martel on Her Controversial Videos for Robin Thicke and Miley Cyrus - Ducker, Eric (Grantland, 2013)
Heads up: NSFW videos and websites are occasionally linked to throughout this post, so watch who’s watching your monitor. Robin Thicke’s “Blurred Lines” and Miley Cyrus’s “We Can’t Stop…

Why Music Matters - Hesmondhalgh, David (John Wiley & Sons, 2013)
Listen to David Hesmondhalgh discuss the arguments at the core of 'Why Music Matters' with Laurie Taylor on BBC Radio 4's Thinking Allowed here. In what ways might music enrich the lives of people and of societies? What prevents it from doing so? Why Music Matters explores the role of music in our lives, and investigates the social and political significance of music in modern societies. First book of its kind to explore music through a variety of theories and approaches and unite these theories using one authoritative voice Combines a broad yet theoretically sophisticated approach to music and society with real clarity and accessibility A historically and sociologically informed understanding of music in relation to questions of social power and inequality By drawing on both popular and academic talk about a range of musical forms and practices, readers will engage with a wide musical terrain and a wealth of case studies
Keywords: Music / General; Music / History & Criticism

Looking for Something New: The Provision of Popular Music Studies Degrees in the UK - Cloonan, Martin; Hulstedt, Lauren (IASPM Journal, 2013)
This article reports the findings of some commissioned research, which was conducted by the authors in 2012. The research sought to examine the extent of Popular Music Studies (PMS) undergraduate programmes in the United Kingdom, determine their key differences, report the findings and make recommendations to the funders about its future policies for PMS practitioners. We report our findings and the implications for PMS practitioners.
Keywords: Popular Music; Teaching; UK; Undergradute

Dark Side of the Tune: Popular Music and Violence - Johnson, Professor Bruce; Cloonan, Professor Martin (Ashgate Publishing, Ltd., 2013)
Written against the academically dominant but simplistic romanticization of popular music as a positive force, this book focuses on the 'dark side' of the subject. It is a pioneering examination of the ways in which popular music has been deployed in association with violence, ranging from what appears to be an incidental relationship, to one in which music is explicitly applied as an instrument of violence. A preliminary overview of the physiological and cognitive foundations of sounding/hearing which are distinctive within the sensorium, discloses in particular their potential for organic and psychic violence. The study then elaborates working definitions of key terms (including the vexed idea of the 'popular') for the purposes of this investigation, and provides a historical survey of examples of the nexus between music and violence, from (pre)Biblical times to the late nineteenth century.The second half of the book concentrates on the modern era, marked in this case by the emergence of technologies by which music can be electronically augmented, generated, and disseminated, beginning with the advent of sound recording from the 1870s, and proceeding to audio-internet and other contemporary audio-technologies. Johnson and Cloonan argue that these technologies have transformed the potential of music to mediate cultural confrontations from the local to the global, particularly through violence. The authors present a taxonomy of case histories in the connection between popular music and violence, through increasingly intense forms of that relationship, culminating in the topical examples of music and torture, including those in Bosnia, Darfur, and by US forces in Iraq and Guantánamo Bay. This, however, is not simply a succession of data, but an argumentative synthesis. Thus, the final section debates the implications of this nexus both for popular music studies itself, and also in cultural policy and regulation, the ethics of citizenship, and arguments about human rights.
Keywords: Music / Ethnomusicology; Music / Instruction & Study / Theory

The Continuum of Sexual Violence: Women’s Accounts of Victimization in Urban Nightlife - Kavanaugh, Philip R. (Feminist Criminology, 2013)
Despite the fact that a substantial amount of research has been conducted on sexual victimization among youth and young adults with active night lives, few of these studies have provided an analysis of the varied types of victimization that have occurred. I attempt to fill this gap with a qualitative analysis of women’s accounts of sexual victimization. Based on the substantive content of these women’s accounts, a three-part typology was generated, comprised of: (a) competing definitions of the situation, (b) opportunistic predation, and (c) involuntary incapacitation. Implications of the findings are discussed.
Keywords: accounts; sexual assault; sexual victimization; unwanted sexual contact

Sexual Orientation & Gender Identity Diversity in Entertainment: Experiences & Perspectives of SAG-AFTRA Members - Badgett, M.V. Lee; Herman, Jody L. (SAG-AFTRA et The Williams Institute, 2013)
Keywords: Bibliographie; Nettoyer; Raphaël

Music, Style, and Aging: Growing Old Disgracefully? - Bennett, Andy (Temple University Press, 2013)
The image of the aging rock-and-roller is not just Paul McCartney and Mick Jagger on stage in their sixties. In his timely book Music, Style, and Aging , cultural sociologist Andy Bennett explains how people move on from youth and effectively grow older with popular music.For many aging followers of rock, punk, and other contemporary popular genres, music is ingrained in their identities. Its meaning is highly personal and intertwined with the individual's biographical development. Bennett studies these fans and how they have changed over time--through fashions, hairstyles, body modification, career paths, political orientations, and perceptions of and by the next generation.The significance of popular music for these fans is no longer tied exclusively to their youth. Bennett illustrates how the music? that "mattered" to most people in their youth continues to play an important role in their adult lives--a role that goes well beyond nostalgia.

Agression sexuelle : L'écrivain Maxime Roussy remis en liberté - Helmlinger, Julien (ActuaLitté, 2013)
Keywords: Bibliographie; Nettoyer

A woman's worth: Analyzing the sexual objectification of Black women in music videos - Ward, L. Monique; Rivadeneyra, Rocio; Thomas, Khia; Day, Kyla; Epstein, Marina (The sexualization of girls and girlhood: Causes, consequences, and resistance, 2013)
One arena where images of sexually objectified women are especially prevalent is the world of music videos. Music videos represent an important area of study, both because of their popularity with younger viewers (Ashby & Rich, 2005) and because love and sex predominate as themes (Andsager & Roe, 1999; Arnett, 2002). What we seek to do here is to take a closer look at the nature and impact of the portrayal of women in music videos, focusing, in particular, on sexually objectifying images. How frequently do objectifying images occur? What messages about femininity do these images convey to girls? What is their demonstrated impact on girls and young women? Given the current popularity of rap and hip-hop music, we focus our attention on their portrayals of African American women. We address these issues via four pathways. First, we summarize findings from existing research concerning the nature of gender portrayals in music videos. Second, we turn our attention to African American artists and summarize findings about the images of black women in music videos. Third, we present new data from an analysis we conducted of the sexual content in black music videos, providing both quantitative and thematic analyses. Finally, we summarize findings about the demonstrated impact of music video exposure on young viewers' gender beliefs and body image concerns. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Blacks; Human Females; Music; Myriam; Objectification; Sex Roles

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Democratising the popular: the case of pop music in France and Britain - Looseley, David L. (International Journal of Cultural Policy, 2012)
The article represents the second phase of a comparative project on French and British cultural policy. The project's guiding hypothesis is that conceptualisations of the popular have been a crucial driver of policy change in France and Britain, raising complex issues about the nature of cultural democracy. The second phase, including this article, takes pop music as a case study for that hypothesis. The article explores three major issues. It asks how and why, in their attempts to rethink cultural democracy for the twenty-first century, French and British policy agencies have recognised pop music as a ‘democratic' form worthy of state support. It critically examines some of the theoretical issues this has raised, comparing and contrasting the ways in which the two national policy sets have variously represented pop as having symbolic, economic and social meanings. And it argues that what has been less adequately addressed is its aesthetic meaning.
Keywords: France and the UK; cultural democracy; pop music

Beyond the Dance Floor: Female DJs, Technology and Electronic Dance Music Culture - Farrugia, Rebekah (Intellect Books, 2012)
A pathbreaking study of the women who create electronic dance music, Beyond the Dance Floor focuses on the largely neglected relationship between these women and the conceptions of gender and technology that continue to inform the male-dominated culture surrounding electronic music. In this volume, Rebekah Farrugia explores a number of important issues, including the politics of identity and representation, the bonds formed by women within the DJ community and the role female DJs and producers play in this dance music culture as well as in the larger public sphere. Though Farrugia primarily focuses on women's relationship to music-related technologies – including vinyl, mp3s and digital production software – she also deftly extends her argument to the strategic use of the Internet and web design skills for purposes tied to publicity, networking and music distribution.
Keywords: Music / Genres & Styles / Electronic; Performing Arts / Dance / General; Social Science / Popular Culture; Social Science / Women's Studies; Technology & Engineering / General

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

The Expansion of Punk Rock: Riot Grrrl Challenges to Gender Power Relations in British Indie Music Subcultures - DOWNES, JULIA (Women's Studies, 2012)

Black Women and Black Men in Hip Hop Music: Misogyny, Violence and the Negotiation of (White-Owned) Space - Rebollo-Gil, Guillermo; Moras, Amanda (Sociology Faculty Publications, 2012)

'Rock On': Women, ageing and popular music - Jennings, R.; Gardner, Abigail ('Rock On': Women, Ageing and Popular Music, 2012)
For female pop stars, whose star bodies and star performances are undisputedly the objects of a sexualized external gaze, the process of ageing in public poses particular challenges. Taking a broadly feminist perspective, 'Rock On': women, ageing and popular music shifts popular music studies in a new direction. Focussing on British, American and Latina women performers and ageing, the collection investigates the cultural work performed by artists such as Shirley Bassey, Petula Clark, Madonna, Celia Cruz, Grace Jones and Courtney Love. The study crosses generations of performers and audiences enabling an examination of changing socio-historical contexts and an exploration of the relationships at play between performance strategies, star persona and the popular music press. For instance, the strategies employed by Madonna and Grace Jones to engage with the processes and issues related to public ageing are not the same as those employed by Courtney Love or Celia Cruz. The essays in this insightful collection reflect on the ways that artists and fans destabilise both the linear trajectories and the compelling weight of expectations regarding ageing by employing different modalities of resistance through persona re-invention, nostalgia, postmodern intertextuality and even early death as the ultimate denial of age.

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
Keywords: Bibliographie; Nettoyer

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies

Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Keywords: France; UK; cultural policy; history; popular culture

‘Guys! Stop Doing It!’: Young Women's Adoption and Rejection of Safety Advice when Socializing in Bars, Pubs and Clubs - Brooks, Oona (The British Journal of Criminology, 2011)
Concern about the increase in alcohol consumption amongst young women, drink spiking and drug-assisted sexual assault have culminated in a renewed focus on safety advice for young women. This paper examines young women's responses to safety advice, and their associated safety behaviours, by drawing upon interview and focus group data from a qualitative study with 35 young women (18–25 years) in relation to their safety in bars, pubs and clubs. The findings reveal that young women's behaviours were complex and contradictory in that they resisted, adopted and transgressed recommended safety behaviours. This raises interesting questions about both the practical and the theoretical implications of contemporary safety campaigns, challenging the prevailing focus on women's behaviour and the gendered discourse invoked by such campaigns.

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

A Safe Education for All: Recognizing and Stemming Harassment in Music Classes and Ensembles - Carter, Bruce Allen (Music Educators Journal, 2011)
This article addresses the pervasiveness of harassment in schools in the United States and presents ways to recognize and stem bullying in music classrooms. Music educators are in a unique position to recognize atypical behaviors in their students. Music educators who teach middle and high school ensembles often retain the same students in their classrooms over the course of many years. Because of the unique nature of the ensemble experience, coupled with the opportunity for extended instruction, music teachers can closely monitor the well-being of their students. However, music teachers should understand how difficult it may be for students who have been harassed to come forward with information about harassment. Sometimes harassment is overt and easy to recognize (e.g., name-calling, inappropriate gestures, graffiti). However, harassment can also occur in contexts that are not readily recognized but are just as hurtful. When students observe teachers taking a stand against bullying and harassment, they recognize the intention for a safe classroom. When students feel safe, they are more likely to ask questions and engage in class in dynamic and meaningful ways—both musically and nonmusically. Only when students feel safe can they learn. Music teachers need to gain a further understanding of various forms of harassment and further consider their role in creating a welcoming and secure environment.
Keywords: Bullying; Harassment; Music classrooms; Myriam

Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Keywords: Bibliographie; Nettoyer

Music festival sponsorship: between commerce and carnival - Anderton, Chris (Arts Marketing: An International Journal, 2011)
Purpose – This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid‐1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach – The paper uses extant research materials to construct an account of British music festival history since the mid‐1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing and branding, in order to understand critiques of corporate sponsorship and the changing nature of the sector. Findings – Outdoor rock and pop music festivals were dominated by the ideologies of a “countercultural carnivalesque” from the late 1960s until the mid‐1990s. In the 1990s, changes in legislation began a process of professionalization, corporatization, and a reliance on brand sponsorships. Two broad trajectories are identified within the contemporary sector: one is strongly rooted in the heritage of the countercultural carnivalesque, while the other is more overtly commercial. Research limitations/implications – It is argued that experiential marketing and brand activation are key methods for achieving a balance between the competing aspects of commerce and carnival. Hence, festival organisers and sponsors need to understand the history of the sector and of their own events and attendees in order to use corporate sponsorship more effectively. Originality/value – This paper adds historical and theoretical depth to the debate between commerce and carnival within the music festival sector, and makes connections between cultural theory and the literature on sponsorship and branding.
Keywords: Bakhtin; Branding; Carnivalesque; Counterculture; Music festivals; Sponsorship; United Kingdom

Popular Music and the State in the UK. Culture, Trade or Industry? by Martin Cloonan - Laing, Dave (Popular Music, 2011)

Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture - Strong, C. (2011)
Semantic Scholar extracted view of "Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture" by C. Strong

Domestic and Sexual Violence and Abuse: Tackling the Health and Mental Health Effects - Itzin, Catherine; Taket, Ann; Barter-Godfrey, Sarah (Routledge, 2010)
Domestic violence, childhood sexual abuse, rape and sexual assault, and sexual exploitation through prostitution, pornography and trafficking can have many significant adverse impacts on a survivor’s health and wellbeing, in the short, medium and long-term. Taking a life-course approach, the book explores what is known about appropriate treatment responses to those who have experienced, and those who perpetrate, domestic and sexual violence and abuse. The book also examines key factors that are important in understanding how and why different groups experience heightened risks of domestic and sexual violence and abuse, namely: gender and sexuality; race and culture; disability; and abuse by professionals. Drawing together results from specially commissioned research, the views of experts by experience, experts by profession and the published research literature, the book argues that sufficient is already known to delineate an appropriate public health framework, encompassing primary, secondary and tertiary prevention, to successfully tackle the important public health issue represented by domestic and sexual violence and abuse. Domestic and Sexual Violence and Abuse equips health and social care professionals and services to identify and respond to the needs of affected individuals with a view to the prevention and early intervention.
Keywords: FAMILY & RELATIONSHIPS; Family & Relationships / Abuse / Child Abuse; Family & Relationships / Abuse / General; Health & Fitness / Women's Health; Medical / Allied Health Services / General; Medical / Health Care Delivery; Psychology / Mental Health; Social Science / Sexual Abuse & Harassment; Social Science / Social Work; Social Science / Violence in Society

Music Education in the 21st Century in the United Kingdom: Achievements, Analysis and Aspirations - Hallam, Susan; Creech, Andrea Ed (Institute of Education - London, 2010)
The landscape of music education in the UK is constantly shifting and developing. This book provides a timely and unique overview of this restless sector by considering the achievements of music education, analysing its current performance and setting out aspirations for the future. "Music Education in the 21st Century in the United Kingdom" addresses the power of music to influence and change human behaviour, analyses current and future issues in music education and casts a spotlight on particular areas of education, including early years, the primary school, the secondary school, further education, universities and conservatoires, music services, the music studio and the role of music leaders and community musicians. Written by experts in the field of music education, the book provides an authoritative account of the current status of music education in the UK. While essential to understand the current and future context in the UK, the book will be invaluable to those involved in music education internationally, as it includes chapters on the provision of music education for all children, listening, the role of singing, playing an instrument, creativity, the role of technology, issues of performance and assessment, learning through the lifespan and the initial and ongoing education of music teachers. It also includes a range of case study examples and evaluations of practice. The book is a landmark publication in the field of music education and will be essential reading for policy-makers, practitioners, music students, trainee music teachers and those who provide music services in the UK and internationally. This book contains three parts. Part I, "Introduction", contains: (1) The power of music: its impact on the intellectual, personal and social development of children and young people (Susan Hallam); and (2) Contextualising music education in the UK (Pauline Adams, Hilary McQueen, and Susan Hallam). Part 2, "Current Issues in Music Education", contains: (3) Music for all (Graham Welch and Adam Ockelford); (4) Listening (Susan Hallam); (5) The role of singing (Jo Saunders, Maria Varvarigou and Graham Welch); (6) Learning to play an instrument (Susan Hallam and Andrea Creech); (7) Creativity (Susan Hallam and Lynne Rogers); (8) The role of technology (Evangelos Himonides and Ross Purves); (9) Issues of assessment and performance (Ioulia Papageorgi and Susan Hallam); (10) Learning through life (Hilary McQueen and Maria Varvarigou); and (11) The initial and ongoing education of music teachers (Colin Durrant and Kate Laurence). Part 3, "Contexts of Learning", contains: (12) Music in the early years (Andrea Creech and Jessica Ellison); (13) Music in the primary school (Jessica Ellison and Andrea Creech); (14) Music in the secondary school (Hilary McQueen and Susan Hallam); (15) Music in further education colleges (John Conlon and Lynne Rogers); (16) Music in universities and conservatoires (Helena Gaunt and Ioulia Papageorgi); (17) Music Services (Lynne Rogers and Susan Hallam); (18) The music studio (Andrea Creech); (19) The role of music leaders and community musicians (Andrea Creech); and (20) Where now? (Susan Hallam and Andrea Creech). This book also contains: Acknowledgements; Preface; Notes on contributors; and Index.
Keywords: Adult Education; Creativity; Early Childhood Education; Educational Trends; Elementary Education; Evaluation; Foreign Countries; Futures (of Society); Higher Education; Individual Development; Inservice Teacher Education; Intellectual Development; Leaders; Lifelong Learning; Listening; Music Education; Music Teachers; Musical Instruments; Musicians; Performance; Preservice Teacher Education; Secondary Education; Singing; Social Development; Technology Uses in Education

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.

Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.